2015
DOI: 10.1051/0004-6361/201525790
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory millimeter wave spectrum and astronomical search for vinyl acetate

Abstract: Context. The recent discovery of methyl acetate in Orion KL makes vinyl acetate, CH 3 C=OOCH=CH 2 , a potential molecule in the interstellar medium. We obtained very accurate spectroscopic constants in a comprehensive laboratory analysis of its rotational spectra which can be used to predict those transition frequencies towards interstellar sources. Aims. We present the experimental study and theoretical analysis of the ground torsional state of vinyl acetate in a large spectral range for astrophysical use. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For calculations of the line strengths, we used the same procedure as the one described in detail in Section 3.2 of (Kleiner 2010). This method had been used for different molecules with C s symmetry containing one methyl rotor such as methyl formate and its isotopologues (Favre et al 2014;Carvajal et al 2009;Haykal et al 2014;Carvajal et al 2007;Tercero et al 2012;Duan et al 2015) or vinyl acetate (Kolesnikova et al 2015). We used the BELGI-C s code to calculate the line strengths, using the energy parameters determined in Table 2.…”
Section: Intensity Calculationmentioning
confidence: 99%
“…For calculations of the line strengths, we used the same procedure as the one described in detail in Section 3.2 of (Kleiner 2010). This method had been used for different molecules with C s symmetry containing one methyl rotor such as methyl formate and its isotopologues (Favre et al 2014;Carvajal et al 2009;Haykal et al 2014;Carvajal et al 2007;Tercero et al 2012;Duan et al 2015) or vinyl acetate (Kolesnikova et al 2015). We used the BELGI-C s code to calculate the line strengths, using the energy parameters determined in Table 2.…”
Section: Intensity Calculationmentioning
confidence: 99%
“…This is demonstrated by first detections of vinylacetylene (C 2 H 3 CCH; Cernicharo et al 2021a), vinylcyanoacetylene (C 2 H 3 C 3 N; Lee et al 2021), and vinylamine (C 2 H 3 NH 2 ; Zeng et al 2021) as well as by observations of excited vibrational states (see, e.g., Belloche et al 2013;López et al 2014) and isotopic species (Müller et al 2008) for vinylcyanide (C 2 H 3 CN): the first vinyl-bearing molecule found in the ISM (Gardner & Winnewisser 1975). Interstellar searches were reported for vinyl formate (C 2 H 3 OCHO; Alonso et al 2016;Coutens et al 2022), vinyl acetate (C 2 H 3 OC(O)CH 3 ; Kolesniková et al 2015), vinyl mercaptan (C 2 H 3 SH; Martin-Drumel et al 2019), vinylisocyanate (C 2 H 3 NCO; Rodríguez-Almeida et al 2021;Vávra et al 2022), acrylic acid (C 2 H 3 C(O)OH; Alonso et al 2015;Calabrese et al 2015;Coutens et al 2022), acrylamide (C 2 H 3 C(O)NH 2 ; Kolesniková et al 2022), and vinyl alcohol (C 2 H 3 OH; Melosso et al 2019). The presence of the latter in the ISM, together with propenal (C 2 H 3 CHO), was announced in the past (Turner & Apponi 2001;Hollis et al 2004) but it has been unambiguously confirmed very recently (Agúndez et al 2021;Manigand et al 2021).…”
Section: Introductionmentioning
confidence: 98%